Podocyte Dedifferentiation: A Specialized Process for a Specialized Cell - May, Carl James; Saleem, Moin; Welsh, Gavin Iain (Frontiers in Endocrinology, 2014)
The podocyte is one of two cell types that contribute to the formation of the glomerular filtration barrier (GFB). It is a highly specialized cell with a unique structure. The key feature of the podocyte is its foot processes that regularly interdigitate. A structure known as the slit diaphragm can be found bridging the interdigitations. This molecular sieve comprises the final layer of the GFB. It is well accepted that the podocyte is the target cell in the pathogenesis of nephrotic syndrome. In nephrotic syndrome the glomerular filtration barrier no longer restricts the passage of macromolecules and protein is lost into the urine. A number of phenotypic and morphological changes are seen in the diseased podocyte and in the literature these have been described as an Epithelial-Mesenchymal Transition (EMT). However, there is a growing appreciation that this term does not accurately describe the changes that are seen. Definitions of type 2 EMT are based on typical epithelial cells. Whilst the podocyte is known as a visceral epithelial cell, it is not a typical epithelial cell. Moreover, podocytes have several features that are more consistent with mesenchymal cells. Therefore we suggest that the term Podocyte Disease Transformation (PDT) is more appropriate.